Kenneth Burke’s Dramatistic Pragmatism: A Missing Link between Classical Greek Scholarship and the Interactionist Study of Human Knowing and Acting - Prus, Robert (Qualitative Sociology Review, 2017)
The term “rhetoric” often has been maligned by those lacking familiarity with classical Greek and Latin scholarship. However, a more sustained, historically-informed examination of persuasive interchange is of fundamental importance for the study of human knowing and acting across the humanities and social sciences, as well as all other realms of community life. While acknowledging several contemporary scholars who have reengaged aspects of classical Greek and Latin rhetoric, this statement gives particular attention to the works of Kenneth Burke and the linkages of Burke’s writings with Aristotle’s Rhetoric, as well as American pragmatist thought and the ethnographically, conceptually-oriented sociology known as symbolic interactionism (Blumer 1969; Strauss 1993; Prus 1996; 1997; 1999; 2015; Prus and Grills 2003). Because scholarship does not exist as isolated instances of genius, even the productions of highly accomplished individuals such as Kenneth Burke are best understood within the context of a horizontal- temporal, as well as a vertical-historical intellectual community. Accordingly, Burke’s contributions to the human sciences more generally and pragmatist social theory (along with its sociological extension, symbolic interaction) more specifically are best comprehended within this broader, historically-enabled scholarly context. Kenneth Burke’s dramatistic pragmatism is not the only missing link between classical Greek thought and symbolic interactionism, but Burke’s work on rhetoric represents a particularly important medium for extending the conceptual and analytic parameters of contemporary symbolic interaction. Indeed, Kenneth Burke’s scholarship has important implications for the fuller study of community life as implied in the most fundamental and enabling terms of human knowing and acting.